2016
DOI: 10.1080/14708477.2016.1168050
|View full text |Cite
|
Sign up to set email alerts
|

Mobile students’ appraisals of keys to a successful stay abroad experience: hints from the IEREST project

Abstract: In order to provide better support for students in higher education throughout a mobility experience, it is important to understand their point of view regarding stay abroad. This paper analyzes the responses of pre-departure, while-abroad, and upon-return students of different academic backgrounds (N = 990) to an open question that asked them to name the three most essential factors for making their stay abroad experience successful. This question was part of a wider online questionnaire distributed in Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…A recently published study has even found that students view personal development and social ties as the most and second-most essential factors, respectively, in a successful semester abroad. Interestingly, academic advantages are considered to be less important (Van Maele et al, 2016). The results found in the present study support the importance of having contact with locals for students' identification with the host country and for their overall satisfaction with their stay.…”
Section: Practical Implicationssupporting
confidence: 76%
See 2 more Smart Citations
“…A recently published study has even found that students view personal development and social ties as the most and second-most essential factors, respectively, in a successful semester abroad. Interestingly, academic advantages are considered to be less important (Van Maele et al, 2016). The results found in the present study support the importance of having contact with locals for students' identification with the host country and for their overall satisfaction with their stay.…”
Section: Practical Implicationssupporting
confidence: 76%
“…Although intergroup contact increased over time, the scores for contact were below the mid-point for each wave of data collection, which means that the students generally had limited sustained contact with host-nationals. This finding is not surprisingly as many studies have shown that international students primarily make friends with co-nationals as opposed to with host-nationals, even if they claim to prefer close contact with host-nationals (e.g., Kashima & Loh, 2006;Van Maele et al, 2016). With ongoing time abroad students had more contact with locals, which was to be expected because of the general assumption that already-existing contacts usually facilitate further contacts and remove obstacles to making friendships with locals, such as language deficits, diminish over time.…”
Section: Summary and Interpretation Of The Findingsmentioning
confidence: 69%
See 1 more Smart Citation
“…As seen in the literature review, the increase in students' mobility can be associated with the expected outcomes acquired or developed during the exchange period, regarded as an initial groundwork for a professional career in a globalized world (IEREST, 2016), fostering independence, confidence and broad-mindedness (Van Maele, Vassilicos, & Borghetti, 2016), while enriching the educacional environment (European Commission, 2015). The scope of developed skills is large, with a clear improvement of intercultural, interpersonal, management, communication and language competences, valued by all as fundamental, and resulting in a better performance and more professional opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…Extant literature provides rich contributions on the motivations to student mobility, including speaking a new language, improving communication abilities, and enrich personal development through independence and confidence (Van Maele, et al, 2016). Mobility is also referred as an opportunity for students to to learn something new about themselves and enhance their cultural horizon.…”
Section: Literature Reviewmentioning
confidence: 99%